Biomonitoring Escherichia coli and Coliform Contamination in Abalone (Haliotis squamata) Cultivation Pond in Musi Village, Gerokgak Sub-District, Buleleng-Bali. - Wiradana, Putu Angga; Yusup, Deny Suhernawan; Soegianto, Agoes (Indonesian Aquaculture Society (MAI), 2019)
Abalone (Haliotis squamata) is one of the fisheries commodities that have high economic value. This study was conducted to investigate contamination of Escherichia coli and coliform in Abalone cultivation ponds in the Musi Village area, Buleleng Regency, Bali. An experiment was carried out by taking water samples in the abalone pond every week for one month. The results showed that there was no difference between the total number of Escherichia coli and coliform. Water samples that were positive for coliform in the determination test had no differences in each sample with total coliform values (Colonies / 100mL) of 4, 3, 7 and 9 (MPN / 100mL) respectively. While the total number of Escherichia coli is shown after being grown in EMBA selective media which are 4, 3, 7, 4 (MPN / 100mL) respectively. Meanwhile, when compared with the number referenced from the Decree of the State Minister of Environment Number 51 of 2004 concerning Sea Water Quality Standards, the quality of seawater for aquatic cultivation in this study is still classified as Safe (<1000 MPN / 100mL).